Prevalent bariatric dietary practices: Is India on the same page? - Ishitaa N Bhatia (Journal of Minimal Access Surgery, 2020)
Background: In the past decade, there has been an increase in the number and types of bariatric procedures in India. It is, thus, important to monitor prevalent bariatric practices. Aim: To identify prevalent pre- and post-operative dietary practices by bariatric professionals across India. Materials and Methods: Data regarding various pre- and post-surgery dietary practices were collected using an Internet-based survey. Thirty-three bariatric professionals including dietitians (n = 25) and surgeons (n = 8) across the country participated in the survey. The data were analysed, and prevalent dietary practices were identified. Results: Five (20%) dietitians were not involved in the pre-surgery consultation. Nineteen (70%) professionals put all patients on a low-calorie pre-surgery diet regardless of their body mass index, with a preference (n = 21; 77.7%) for liquid diet. Twenty-three (70%) professionals put patients on post-surgery liquid diet for 1–2 weeks. Thereafter, 28 (84.8%) professionals recommended soft diet for 2–4 weeks. Twenty-seven (81%) professionals used protein shakes (as opposed to dietary sources) as their primary source of protein for the first 3 months post-surgery. Fourteen (36%) professionals stopped protein shake supplements within 6 months post-surgery. Ten (30%) professionals reported whey protein aversions in >25% of the patients. Twenty-three (71%) professionals advocated a meal with <30% of carbohydrates for up to 1 year. Twenty-eight (84%) professionals used portion control method for meals. Conclusion: Our study reflects that prevalent dietary practices among Indian bariatricians are in line with national and international guidelines.